Validation of distant metastases risk-groups in oral cavity squamous cell carcinoma patients treated with postoperative intensity-modulated radiotherapy. (May 2019) - Hosni, Ali; Huang, Shao Hui; Chiu, Kevin; Xu, Wei; Su, Jie; Lu, Lin; Bayley, Andrew; Bratman, Scott V.; Cho, John; Giuliani, Meredith; Kim, John; O'Sullivan, Brian; et al.
Highlights: This study validated a high DM risk-group in OSCC patients treated with postoperative IMRT with or without concurrent chemotherapy. Patients with G2-3/pN2-3 were shown to be at high risk of DM and poor survival in the subsequent validation cohort. Identifying this high risk group may allow alternate treatment strategies to be explored to improve the outcomes. Abstract: Background: This study aimed to derive distant metastases (DM) risk-groups in oral cavity squamous cell carcinoma (OSCC) patients treated with postoperative intensity-modulated radiation therapy (PO-IMRT). Methods: OSCC patients treated with PO-IMRT were divided into discovery (2005–2012) and validation (2013–2014) cohorts. DM predictors were identified from multivariable analysis (MVA) to derive low- and high-risk groups in the discovery-cohort. The result was subsequently evaluated in validation-cohort. Results: Overall 447 patients were included (discovery-cohort: n = 300, and validation-cohort: n = 147). Between the two cohorts, there were no significant differences in DM ( p = 0.16) or OS ( p = 0.26). MVA identified pN2-3 and histological grade 2–3 (G2-3) as DM predictors. High-risk group included patients who had both poor predictors (pN2-3 and G2-3), while low-risk group included patients with no or only one poor predictor. In discovery-cohort, 3-year distant control (DC) was 78% and 97% in high- and low-risk groups respectively ( p < 0.001, concordance index = 0.72). In validation-cohort, risk-group classification performed similarly (concordance index = 0.73). The 3-year OS for high- versus low-risk group was 85% versus 95% in discovery-cohort ( p < 0.001), and 74% versus 93% in validation-cohort ( p < 0.001). Conclusion: A model (G2-3/pN2-3) which identifies high DM risk was validated internally. This model might be used to design future prospective studies investigating treatment intensification and/or DM surveillance.